Media education in Waldorf/Steiner schools - Neumann, Robert (Frontiers in Education, 2024)
This article explores the distinctive approach to media education in Steiner/Waldorf Schools, focusing on delayed introduction of electronic media. Addressing a research gap, the article highlights the unique developmental phases guiding media pedagogy, combining direct and indirect media education and the so called "media maturity tower". A central focus is the alignment of media pedagogy with the cognitive developmental stages of students. There are three distinct phases addressed in connection with different topics within the school curriculum.These phases underscore the educational commitment to age-appropriate media engagement and enable a comparison between the rather critical stance of taken by Steiner/Waldorf Schools and the current trends regarding the use of media in education.The article highlights the need for further research on the long-term impact of the developmental approach here described on students' media interactions in adulthood.